GAMBARAN RESILIENSI DAN HARGA DIRI RENDAH PADA REMAJA YANG TINGGAL DI PANTI ASUHAN NAZARET TOMOHON : STUDI KUALITATIF - Evita Sophitje Tumoka; Andi Buanasari; Hendro Bidjuni (JURNAL KEPERAWATAN, 2022)
Background Adolescent are prone to psychosocial or behavioral problems one of which is low self esteem. Adolescent in orphanages tends to have low self esteem, so it is necessary to increase resilience to overcome the low self-esteem experienced by adolescent. The Purpose of this study to get an overview of the Resilience and low self-esteem of adolescent in Nazaret Tomohon orphanage. This Method study uses a qualitative research method with a phenomenological approach. Sampling used purposive sampling involving 11 participants. Analysis of the data used based on the Colaizzi model. The Results of this study obtained three themes, 1) the causes of low self-esteem in adolescent, 2) the impact of low self-esteem and low Resilience in adolescent 3) efforts to increase Resilience in overcoming low self-esteem. The Conclusion Low self-esteem experienced by adolescent will have an impact on internal and external behavioral problems (juvenile delinquency). So that efforts are needed to increase resilience to overcame self esteem experienced by making programs or policies to provide counseling services to adolescent increasing self esteem and resilience.